IMPLEMENTASI PENDEKATAN DEEP LEARNING PADA PELAJARAN AKIDAH AKHLAK DI MAN 1 KOTA TANGERANG SELATAN - Ahmad Rafi Al Hazmi (As-Sulthan Journal of Education, 2025)
The current educational transformation is the background of this research conducted at MAN 1 South Tangerang City. Deep learning as the latest learning approach is a formula for low student interest and enthusiasm. Conventional learning methods cause boredom in students. Therefore, deep learning is implemented to be a solution. This research was conducted using classroom action research (CAR) with an experimental approach. The purpose of this study was to determine the effectiveness of the application of deep learning in learning aqidah akhlak in class X MAN 1 South Tangerang City. The results of this study indicate that deep learning can foster collaboration, creativity, and critical thinking of students and make learning aqidah akhlak mindful, meaningful, and enjoyable learning.